Dexmedetomidine and the Combination of Benzodiazepine and Fentanyl in Elective Endovacular Stenting of the Coronary Arteries. Comparative Analysis - A. V. Tsarkov; A. L. Levit (Вестник анестезиологии и реаниматологии, 2022)
The optimal method of anesthetic management in percutaneous coronary interventions (PCI) is procedural analgosedation that in most cases is provided by the combination of benzodiazepine and an opioid analgesic. However, there are no protocols and recommendations for its implementation at this time.The objective: to choose an adequate and safe method of analgosedation for elective endovascular stenting of coronary arteries.Subjects and Methods. A randomized study was conducted from September 2021 to January 2022. The group where analgosedation with fentanyl and sibazon was used included 33 patients. 30 patients were enrolled in the group of analgosedation with dexmedetomidine. A comparison was made in terms of the level of sedation (RASS scale), hemodynamic parameters, blood oxygen saturation (SpO2), the incidence of anginal pain at the stage of stenting and the need for additional analgesia, and the level of serum troponin T.Results. Dexmedetomidine significantly induces a deeper level of sedation (RASS -2) compared to the combination of benzodiazepine and fentanyl (RASS -1) at the stage of intracoronary stent placement (p < 0.001). In the group of analgosedation with dexmedetomidine, there was a statistically significant decrease in blood pressure and heart rate versus the group of analgosedation with fentanyl and sibazon (p < 0.05). Analgesia with narcotic analgesics was required 9.1 times lower (p =0.028) at the stage of installation of intracoronary stents in the group of dexmedetomidine analgosedation versus the group of fentanyl and sibazon analgosedation (OR 0.11; 95% CI 0.13–0.92).Conclusion. Anesthesia for elective percutaneous coronary interventions with dexmedetomidine may be more adequate and safer than the combination of a benzodiazepine and an opioid analgesic. At the stage of coronary artery stenting, dexmedetomidine provides deeper sedation, significant prevention of the development of anginal pain, a pronounced hypotensive and negative chronotropic effect compared to analgosedation with fentanyl and sibazon.